Zonnic®: a new player in an old field - Min Gong; Michael S. Dunbar; Claude Setodji; William G. Shadel (BMC, 2017)
Abstract The tobacco industry is continually evolving to adapt to increasing tobacco control pressure and regulation, and to cater to consumer preferences. Recently, RJ Reynolds rolled-out a nicotine-containing gum, Zonnic®, which is marketed as a smoking cessation and reduction product and is sold at convenience stores at a lower price and in a smaller quantity than existing brands sold at pharmacies. The introduction of Zonnic® products is a critical first step in tobacco industry's involvement in the NRT market and a serious indication of the evolving tobacco and nicotine-delivery industry and environment. It is likely that this trend will continue and spread, and as such, have a significant impact at multiple dimensions, including consumer perceptions and behavior, tobacco and NRT industry business strategy, and regulation and policy. In this special communication, we present an overview of the current marketing strategy for Zonnic®, discuss its potential impacts at the market level and at the level of the individual consumer, and suggest research and policy priorities based on the magnitude and urgency of the impacts.